Allies that count : junior partners in coalition warfare - Schmitt, Olivier, 1987- (Georgetown University Press, 2018)
What qualities make an ally useful in coalition warfare, and when is an ally more trouble than its worth? This book analyzes the utility of junior partners in coalition warfare and reaches surprising conclusions. Olivier Schmitt conducts detailed case-study analysis of several US allies in the Gulf War, the Kosovo campaign, the Iraq War, and the war in Afghanistan. He also does a broader analysis of 204 junior partners in various interventions since the end of the Cold War. Schmitt aims to bridge a gap in previous studies about coalition warfare, while also contributing to policy debates about a recurring defense dilemma. Previous works about coalition warfare have focused on explaining how coalitions are formed, but little attention has been given to the issue of their effectiveness. At the same time, policy debates, have framed the issue of junior partners in multinational military operations in terms of a trade-off between the legitimacy that is allegedly gained from a large number of coalition states vs. the decrease in military effectiveness associated with the inherent difficulties of coalition warfare. Schmitt determines which political and military variables are more likely to create utility, and he challenges the conventional wisdom about the supposed benefit of having as many states as possible in a coalition.